2005
DOI: 10.1261/rna.7215305
|View full text |Cite
|
Sign up to set email alerts
|

Binding of eukaryotic initiation factor 3 to ribosomal 40S subunits and its role in ribosomal dissociation and anti-association

Abstract: The multisubunit eukaryotic initiation factor (eIF) 3 plays various roles in translation initiation that all involve interaction with 40S ribosomal subunits. eIF3 can be purified in two forms: with or without the loosely associated eIF3j subunit (eIF3j+ and eIF3j−, respectively). Although unlike eIF3j+, eIF3j− does not bind 40S subunits stably enough to withstand sucrose density gradient centrifugation, we found that in addition to the known stabilization of the eIF3/40S subunit interaction by the eIF2·GTP·Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
134
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(147 citation statements)
references
References 76 publications
(116 reference statements)
12
134
1
Order By: Relevance
“…eIF3 is a canonical initiation factor that interacts with the 40S subunit (8,9). Enrichment of DHX29 in 40S fractions in vivo is in agreement with the in vitro data (7) and consistent with the suggested function of DHX29 at the translation initiation stage.…”
Section: Dhx29 Is a Ubiquitously Expressed Cytoplasmic Protein That Asupporting
confidence: 88%
“…eIF3 is a canonical initiation factor that interacts with the 40S subunit (8,9). Enrichment of DHX29 in 40S fractions in vivo is in agreement with the in vitro data (7) and consistent with the suggested function of DHX29 at the translation initiation stage.…”
Section: Dhx29 Is a Ubiquitously Expressed Cytoplasmic Protein That Asupporting
confidence: 88%
“…eIF3 also impedes 40S-60S subunit association. 42,43 Studies in a reconstituted yeast system have shown that eIF3 (and eIF5) enhances TC binding to the 43S initiation complex. 25,[44][45][46] In addition, genetic and biochemical data have shown that eIF3 can exist as part of a MFC along with eIF1, eIF5 and TC prior to 43S/48S complex formation.…”
Section: E999576-4mentioning
confidence: 99%
“…Although eIF3j is a component of a binary eIF3⅐40 S complex, it is no longer associated with eIF3 and the 40 S subunit in the presence of mRNA as well as in 48 S complexes (4,28). In such ribosomal particles lacking eIF3j, interactions of eIF3a, eIF3b, and eIF3d with mRNA (28) might then instead support the stable association of eIF3 with the 40 S subunit and thereby replace the requirement of eIF3j for stable eIF3/40 S binding.…”
Section: Eif3b-rrm Resembles Noncanonical Rrms Of the U2afmentioning
confidence: 99%
“…The initiation phase of protein synthesis requires at least 12 eukaryotic initiation factors (eIFs) 4 to assemble 80 S ribosomes onto mRNA with the anticodon of tRNA i Met base-paired to the authentic AUG start codon (for a review, see Ref. 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation